2013
DOI: 10.5142/jgr.2013.37.117
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of polyphenol oxidase from fresh ginseng

Abstract: Polyphenol oxidase (PPO) was purified from fresh ginseng roots using acetone precipitation, carboxymethyl (CM)-Sepharose chromatography, and phenyl-Sepharose chromatography. Two isoenzymes (PPO 1 and PPO 2) were separated using an ion-exchange column with CM-Sepharose. PPO 1 was purified up to 13.2-fold with a 22.6% yield. PPO 2 bound to CM-Sepharose, eluted with NaCl, and was purified up to 22.5-fold with a 17.4% yield. PPO 2 was further chromatographed on phenyl-Sepharose. The molecular weight of the purifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
6
2
Order By: Relevance
“…In contrast, the yield of sPPO2 was 2.10%, and the sPPO2 specific activity was 53,463.16 U/mg. Compared to previous literature reports, the fold-purification was 5.14 higher than reported for the PPO from potato (Aksoy, 2020), 19.77-fold higher than for the PPO from tea leaf (Camellia sinensis) (Öztürk, Aksoy, & Küfrevioğlu, 2019), 13.3 and 22.5 than for the PPO from Ginseng (Kim & Kim, 2013), and 12.38 higher than for the PPO from Indian pink guava (Vishwasrao & Ananthanarayan, 2018). The recovery rate was higher than for the PPO from mamey fruit (Pouteria sapota) which was 0.28% (Orozcoa, Moreno, Álvarez, Sampedrob, & Nájerac, 2011) and close to the recovery rate of 2.03% seen for the PPO from chestnut kernel (Gong, Li, Liu, Cheng, & Wang, 2015)…”
Section: Separation and Purification Of Mppo And Sppocontrasting
confidence: 63%
“…In contrast, the yield of sPPO2 was 2.10%, and the sPPO2 specific activity was 53,463.16 U/mg. Compared to previous literature reports, the fold-purification was 5.14 higher than reported for the PPO from potato (Aksoy, 2020), 19.77-fold higher than for the PPO from tea leaf (Camellia sinensis) (Öztürk, Aksoy, & Küfrevioğlu, 2019), 13.3 and 22.5 than for the PPO from Ginseng (Kim & Kim, 2013), and 12.38 higher than for the PPO from Indian pink guava (Vishwasrao & Ananthanarayan, 2018). The recovery rate was higher than for the PPO from mamey fruit (Pouteria sapota) which was 0.28% (Orozcoa, Moreno, Álvarez, Sampedrob, & Nájerac, 2011) and close to the recovery rate of 2.03% seen for the PPO from chestnut kernel (Gong, Li, Liu, Cheng, & Wang, 2015)…”
Section: Separation and Purification Of Mppo And Sppocontrasting
confidence: 63%
“…The initial velocity was calculated from the slope of the absorbance value against time curve. One unit (U) of PPO activity was defined as amount of enzyme that caused a 0.001 absorbance change per min (Kim and Kim 2013).…”
Section: Ppo Assaymentioning
confidence: 99%
“…Voss], it was found that L-cysteine showed the best inhibitory effect, with an IC50 of 1.3±0.002 mM followed by ascorbic acid (1.5 ± 0.06 mM), glutathione (1.5 ±0.07 mM), EDTA (100 ±0.02 mM) and citric acid (186±0.16 mM). It was reported that Ginseng PPO activity was inhibited by ascorbic acid, sodium metabisulfite, and kojic acid, using catechol as the substrate, whereas 1 mM citric acid showed slight activation rather than inhibition for the ginseng PPO [18]. …”
Section: Effect Of Inhibitorsmentioning
confidence: 98%